Family, firms and the gender wage gap in France - Elise Coudin; Sophie Maillard; Maxime Tô (Institute for Fiscal Studies (IFS), 2018)
In France, in 2014, women's hourly wages were on average 14.4 % lower than men's. Beyond differentials in observed characteristics, is this gap explained by segregation of women in low-wage firms, or by gender inequality within a given firm? To answer that question, we apply the approach of Card, Cardoso, and Kline (2016) on French data to disentangle the role of between-firm (sorting) and within-firm heterogeneity (bargaining) on the gender wage gap. We use a two-way fixed effect wage model, in which firm fixed effects differ between male and female employees to account for within-firm gender differences in bargaining power and wage policy. We estimate this model with linked employer-employee data covering French private sector from 1995 to 2014. The sorting effect accounts for almost 11% of the gender wage gap, whereas the bargaining effect is close to zero. This last result could be related to the protective role of the high French minimum wage level. We have access to very rich administrative data that allow us to recover information on family events. Hence, we can analyze sorting and bargaining effects all along the family life cycle. Our analysis shows that firm effect gap appears clearly around the first childbirth and deepens over the life cycle: in addition to the direct effects of childbirth on wages, mothers also experience wage losses associated to sorting into low-paying firms.
Keywords: J31; J71; J16; 330; gender wage gap; gender inequalities; linked employer-employee data; two-way fixed effect models; discrimination